Multilevel converter to access maximum power from distributed energy source based smart grids - Alkhaledi, Khaled; Cheema, Khalid Mehmood; Elbarbary, Z. M. Salem; Park, Woo-Hyung; El-Sherbeeny, Ahmed M. (Frontiers in Energy Research, 2023)
The distributed power generation is increasing rapidly, and its integration into the power system is a critical issue for the existing power network. Therefore, a three-level converter is developed to access and control the medium voltage DC generated from a photovoltaic system in a smart grid. A conventional three-level neutral point clamped circuit is incorporated into the conventional inverter. The conventional inverter is a pulse width modulation-based inverter that achieves zero switching currents and supplies power to the load. This technique suppresses the switching power loss up to a large extent. Additionally, switches conduct half of the input voltage; therefore, the output voltage is significantly similar to the voltage of the output filter. Moreover, in the proposed converter, the stress of voltage on diodes is minimal, which increases the input range of voltage in smart grids. The overall efficiency of converter is around 97.9% and voltage gain is around 42. In addition to these, a detailed design description and analysis are carried out in this paper. In the end, a prototype is developed for experimental analysis to validate the operating principle and characteristics of the proposed converter.